The problem of the lower boundary of the Pleistocene in Eastern Lithuania. (2nd November 2015) - Bitinas, Albertas; Katinas, Valentas; Gibbard, Philip L.; Saarmann, Simonas; Damušytė, Aldona; Rudnickaitė, Eugenija; Baltrūnas, Valentinas; Satkūnas, Jonas
Abstract: A sequence of lacustrine and alluvial sediments represented by stratified sand, silt and, rarely, clay over 20 m-thick is widespread in the Anykščiai and Vilnius districts in Eastern and South-eastern Lithuania, respectively. These sediments are exposed only in Eastern Lithuania, in the Šventoji River valley and its tributaries. Here they overlie Devonian bedrock and are overlain by the Pleistocene glacial deposits. The results of different geological investigations (palaeobotanical, mineralogical, geochemical, etc.) indicate that these sediments probably formed in the basins and rivers that date from the Neogene to the Early Pleistocene. Stratigraphical subdivision and correlation of sediments from the transition zone between the Neogene and Quaternary are problematic for several reasons. This article presents new results of palaeomagnetic investigations of these sediments from five outcrops, accompanied by lithological studies. The sediments were laid down during a relatively long and variable period of palaeomagnetic reversals comparable to the Matuyama and Gauss polarity chrons. The boundary between the Brunhes and Matuyama polarity chrons has been traced in the upper part of the sections. The stratigraphical subdivision and correlation of the entire sequence, as well as the identification of the Neogene/Quaternary boundary in these sediments, remain undetermined.